2022
DOI: 10.1097/md.0000000000030227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of continuous intravenous lidocaine on brain relaxation, intraoperative opioid consumption, and surgeon’s satisfaction in adult patients undergoing craniotomy tumor surgery: A randomized controlled trial

Abstract: Background: In craniotomy tumor removal, brain relaxation after dura opening is essential. Lidocaine is known to have analgesic and antiinflammatory effects. It is excellent in decreasing cerebral metabolic rate of oxygen, cerebral blood flow, and cerebral blood volume; and can potentially reduce intracranial pressure, resulting in exceptional brain relaxation after dura opening. However, no study has examined continuous intravenous lidocaine infusion on brain relaxation, intraoperative opioid consumption and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Lidocaine infusion has demonstrated efficacy as a co-analgesic in various surgical populations that include both intracranial and spine surgery patients. 25,26 While its exact mechanism of action remains elusive, it has been postulated that lidocaine exerts its antinociceptive, antiinflammatory, and anti-hyperanalgesic properties through both central and peripheral pathways. 27 Earlier studies reported conflicting effects of lidocaine infusions on IONM when used in clinically relevant doses, and a possible depression of signals has been postulated to be the result of partial inactivation of sodium channels.…”
Section: Lidocainementioning
confidence: 99%
See 1 more Smart Citation
“…Lidocaine infusion has demonstrated efficacy as a co-analgesic in various surgical populations that include both intracranial and spine surgery patients. 25,26 While its exact mechanism of action remains elusive, it has been postulated that lidocaine exerts its antinociceptive, antiinflammatory, and anti-hyperanalgesic properties through both central and peripheral pathways. 27 Earlier studies reported conflicting effects of lidocaine infusions on IONM when used in clinically relevant doses, and a possible depression of signals has been postulated to be the result of partial inactivation of sodium channels.…”
Section: Lidocainementioning
confidence: 99%
“…Lidocaine infusion has demonstrated efficacy as a co-analgesic in various surgical populations that include both intracranial and spine surgery patients 25,26. While its exact mechanism of action remains elusive, it has been postulated that lidocaine exerts its antinociceptive, anti-inflammatory, and anti-hyperanalgesic properties through both central and peripheral pathways 27.…”
Section: Current Evidencementioning
confidence: 99%